Analisis kemampuan berpikir logis siswa 1G Madrasah Mu’allimin Muhammadiyah Yogyakarta tahun akademik 2022/2023 - Muflih Abdullah Zufar; Dwi Astuti (Math Didactic: Jurnal Pendidikan Matematika, 2023)
Education is a systematic effort to develop individual abilities in the era of globalization. According to Law Number 20 Article 3 of 2003 education has a strategic function in preparing high intellectual, emotional and social abilities. Thinking ability affects success in learning. Thinking is the process of interpreting circumstances from existing premises. Logical thinking becomes a step in solving complex problems for every individual. Mathematics affects the formation of a mindset. The ability to think logically is based on indicators in making meaning, making logical connections between concepts and facts, grieving and testing concepts, solving problems rationally, and drawing conclusions. The research was conducted on seventh-grade G-class students of Madrasah Mu'allimin Muhammadiyah Yogyakarta using test and interview methods as confirmation. Student work results were analyzed descriptively and grouped into four categories in general and based on indicators. It was found that students' abilities were in the less high category with a percentage of 76.7% and based on indicators the majority were in the less high category. So, it can be concluded that student’s ability to think logically is low.